Presynaptic congenital myasthenic syndrome with a homozygous sequence variant in LAMA5 combines myopia, facial tics, and failure of neuromuscular transmission. Issue 8 (25th May 2017) - Maselli, Ricardo A.; Arredondo, Juan; Vázquez, Jessica; Chong, Jessica X.; ,; Bamshad, Michael J.; Nickerson, Deborah A.; Lara, Marian; Ng, Fiona; Lo, Victoria L.; Pytel, Peter; McDonald, Craig M.
Abstract : Defects in genes encoding the isoforms of the laminin alpha subunit have been linked to various phenotypic manifestations, including brain malformations, muscular dystrophy, ocular defects, cardiomyopathy, and skin abnormalities. We report here a severe defect of neuromuscular transmission in a consanguineous patient with a homozygous variant in the laminin alpha‐5 subunit gene ( LAMA5) . The variant c.8046C>T (p.Arg2659Trp) is rare and has a predicted deleterious effect. The affected individual, who also carries a rare homozygous sequence variant in LAMA1, had muscle weakness, myopia, and facial tics. Magnetic resonance imaging of brain showed mild volume loss and periventricular T2 prolongation. Repetitive nerve stimulation revealed 50% decrement of compound muscle action potential amplitudes and 250% facilitation immediately after exercise, Endplate studies identified a profound reduction of the endplate potential quantal content and endplates with normal postsynaptic folding that were denuded or partially occupied by small nerve terminals. Expression studies revealed that p.Arg2659Trp caused decreased binding of laminin alpha‐5 to SV2A and impaired laminin‐521 cell‐adhesion and cell projection support in primary neuronal cultures. In summary, this report describing severe neuromuscular transmission failure in a patient with a LAMA5 mutation expands the list of phenotypes associated with defects in genes encoding alpha‐laminins.